Spatiotemporal Modeling of Lifting Task Scheduling for Tower Cranes With a Tabu Search and 4-D Simulation - Wu, Keyi; García de Soto, Borja (Frontiers in Built Environment, 2020)
Effective lifting task scheduling for tower cranes is beneficial for the smooth operation of a construction project. Previous studies have often ignored workspace availability for lifting task scheduling. Consequently, the pre- and post-lifting processes that are primarily caused by material preparation and transfer times at supply and demand points were not considered. Therefore, an intuitive and effective way to display more element information of lifting tasks and more complex relationships among lifting tasks is required. To solve these problems, this study proposes a spatiotemporal modeling of lifting task scheduling for tower cranes, which consists of a lifting task scheduling optimization model with a tabu search and a lifting task scheduling display method with 4-D simulation. The concept of the proposed spatiotemporal modeling is demonstrated by an example with 28 lifting tasks and two tower cranes. The results show that the average total time of the optimized lifting task scheduling, taking into consideration the material preparation and transfer times at the supply and demand points, can be reduced by 25.82%. In addition, the element information and relationship of lifting tasks can be clearly presented using the proposed display method with 4-D simulation.